2012
DOI: 10.1007/s00424-012-1184-x
|View full text |Cite
|
Sign up to set email alerts
|

A conserved threonine in the S1–S2 loop of KV7.2 and KV7.3 channels regulates voltage-dependent activation

Abstract: The voltage-gated potassium channels KV7.2 and KV7.3 (KCNQ2/3 genes) play an important role in regulating neuronal excitability. More than 50 KCNQ2/3 mutations have been identified to cause an inherited form of epilepsy in newborns. For two of those (E119G and S122L) found in the S1-S2 region of KV7.2, we previously showed a decreased channel availability mainly at action potential subthreshold voltages caused by a slight depolarizing shift of the activation curve. Interestingly, recent studies revealed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The T210K/M variants resulted in loss of K + conductance and cell‐surface K V 2.1 expression. T210 is a critical residue forming the S1–pore interface . A hydroxyl group is required at this position for channel function .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T210K/M variants resulted in loss of K + conductance and cell‐surface K V 2.1 expression. T210 is a critical residue forming the S1–pore interface . A hydroxyl group is required at this position for channel function .…”
Section: Discussionmentioning
confidence: 99%
“…T210 is a critical residue forming the S1-pore interface. 31,32 A hydroxyl group is required at this position for channel function. 32 Thus, substitution with either lysine or methionine would be incompatible with channel function.…”
Section: Comparison Of Same-site Substitutionsmentioning
confidence: 99%
“…1a,b) and has been implicated as a candidate for a functional VSD-to-pore domain connection2032. Further, residues in the neighborhood of F416 form an important, close, and rigid contact point between the VSD and the pore domain3334353637. Here we explore the hypothesis that residue F416 is a possible candidate in the reciprocal VSD-to-pore interaction that modulates C-type inactivation.…”
mentioning
confidence: 97%
“…K + channel alterations may reflect the clinical antinociceptive action. A number of studies have shown that voltage-gated K + channels have a major role in the regulation of neuronal excitability (21,22). …”
Section: Discussionmentioning
confidence: 99%